A targeted complement-dependent strategy to improve the outcome of mAb therapy, and characterization in a murine model of metastatic cancer - Elvington, Michelle (American Society of Hematology, 2012)
Complement inhibitors expressed on tumor cells provide an evasion mechanism against mAb therapy and may modulate the development of an acquired antitumor immune response. Here we investigate a strategy to amplify mAb-targeted complement activation on a tumor cell, independent of a requirement to target and block complement inhibitor expression or function, which is difficult to achieve in vivo. We constructed a murine fusion protein, CR2Fc, and demonstrated that the protein targets to C3 activation products deposited on a tumor cell by a specific mAb, and amplifies mAb-dependent complement activation and tumor cell lysis in vitro. In syngeneic models of metastatic lymphoma (EL4) and melanoma (B16), CR2Fc significantly enhanced the outcome of mAb therapy. Subsequent studies using the EL4 model with various genetically modified mice and macrophage-depleted mice revealed that CR2Fc enhanced the therapeutic effect of mAb therapy via both macrophage-dependent FcγR-mediated antibody-dependent cellular cytotoxicity, and by direct complement-mediated lysis. Complement activation products can also modulate adaptive immunity, but we found no evidence that either mAb or CR2Fc treatment had any effect on an antitumor humoral or cellular immune response. CR2Fc represents a potential adjuvant treatment to increase the effectiveness of mAb therapy of cancer.